BIS:an RFID anti-collision algorithm minimizing the cost of empty slots - WANG Zhong-xiang; WANG Jun-yu; LIU Dan; MIN Hao (Tongxin xuebao)
A novel ALOHA-based medium access control（MAC） protocol, BIS, was proposed, in which the time consumption of the empty slots had been largely reduced through empty slot scanning and dynamic frame size adjustment.According to the simulation results, the system efficiency and identification speed of BIS algorithm are efficiently improved, compared to those of the normal ALOHA-based algorithms and tree-based algorithms.